PENINGKATAN PARTISIPASI MASYARAKAT DALAM LITERASI, KEBERSIHAN LINGKUNGAN, KESEHATAN JASMANI DI DESA KUTA JURUNG - Ely Ezir Marpaung; Elia Maynita Karo-karo; Friska Jayanti Sihombing; Valentina Purnama Sari Limbong; Vianny R Pardosi (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2026)
The PkM activities conducted by the Faculty of Teacher Training and Education in Kuta Jurung Village aim to address real issues faced by the community, particularly in the areas of literacy, environmental cleanliness, physical health, and the utilization of digital learning media. This program was designed with several core activities, including tutoring for students, communal clean-up efforts (gotong royong), the implementation of posyandu (integrated health services) as a form of public health education, and training in the use of digital media. The methods used involved direct observation, followed by preparation, implementation, and reporting stages. The program was carried out at the village office and student post from January to February 2025. The results showed an increase in student learning motivation and academic performance through tutoring. Gotong-royong helped create a cleaner environment and strengthened community social ties. The posyandu played a vital role in raising awareness of maternal and child health, as well as in supporting malnutrition prevention and child growth monitoring. The production and distribution of homemade dish soap (Sunlight), along with hygiene education, raised awareness of the importance of household sanitation.  The success of this program is expected to serve as a model for similar initiatives in other regions.